Environmentally Induced Oxidative Stress and Disruption of Brain Thyroid Hormone Homeostasis in Autism Spectrum Disorders - Sajdel-Sulkowska, Elizabeth M. (IntechOpen, 2011)
In memory of my son and a budding neuroscientist, Zachary L. Sulkowski, BS